KONSTRUKSI DAN PRODUKTIVITAS RUMPON PORTABLE DI PERAIRAN PALABUHANRATU, JAWA BARAT - Roza Yusfiandayani; Indra Jaya; Mulyono S Baskoro (Fakultas Perikanan dan Ilmu Kelautan, 2014)
Fish Aggregating Device (FAD) usually used by small and large scale fishermen in Indonesia are FAD shallow and deep sea water which fix in the water. Effectiveness and efficiency research activity about portable FAD in the water to catch Thunnus spp. and skipjack have never been done in Indonesia. This research divided into two stages : portable FAD design, fishing trial with portable FAD used handline and troll line in Palabuhanratu waters. The purpose of this research was to make portable FAD design, fishing trial used Electric Fish Attractor (EFA) with different frequency and to compared effectiveness of catch composition with handline and troll line. The result of this study were design FAD portable with length and width 1 m, the material is manglid wood, the attractors are raffia line and attractor and sinker line used PE with diameter 4 mm and tin sinker, EFA with frequency 10-1.000 Hz catch Caranx fasciatus and Trichiurus sp., whereas EFA with frequency 1.000-20.000 Hz catch 2 fish of Thunnus albacares with length 30 cm and weight 40 kg, catch composition used handline was Trichiurus sp. 63%, Nemiptarus sp. 10%, Caesio cuning 7%, Euthynnus spp. and semar 4%, Lutjanus spp. and Thunnus albacares 2%, whereas catch composition with troll line was Rastrelliger spp, Caesio cuning, and Selaroides spp. 1%.